Determination of Selected Heavy Metals in Sediments from Paka River and Kerteh River - Jaafar, Nurul Fazlina (2016)
Heavy metals pollution becomes worldwide issues because it causes harmful to living organisms and to the environment. Heavy metal can be defined as any metallic elements that have a relatively high density and it can also defined as toxic and poisonous although it at low concentration. The objectives of this study were to determinate the concentration of selected heavy metal in sediment from Paka River and Kerteh River and to compare selected heavy metal concentration with Consensus-Based Sediment Quality Guideline (CBSQG). Eleven heavy metals (Fe, Cu, Ni, Zn, Mn, K, Na, Mg, Ag, Cr, and Hg) were analyzed by using atomic absorption spectrometry (AAS). From this study, the heavy metal concentrations for Fe, Cu, Ni, Zn, Mn, K, Na, Mg, Ag, Cr, and Hg were ranged between 722.77 mg/L to 10113 mg/L, 0.13 mg/L to 2.06 mg/L, 0.00 mg/L to 0.31 mg/L, 0.79 mg/L to 3.77 mg/L, 0.65 mg/L to 10.34 mg/L, 48.71 mg/L to 280.23 mg/L, 194.83 mg/L to 862.13 mg/L, 223.6 mg/L to 2769 mg/L, 0.00 mg/L to 0.03 mg/L, 0.15 mg/L to 1.12 mg/L and 0.33 mg/L to 8.00 mg/L respectively. Generally, the decrease order observes for this study were, Fe>Mg>Na>K>Mn>Hg>Zn>Cu>Cr>Ni>Ag and the highest concentration of Fe shown in SK A meanwhile the lowest concentration of Ag shown in SK B. For CBSQG shown, the value that recommended is lower than the value of concentration at the sampling site except for Hg concentration. This study had shown that all the station shown higher concentration than CBSQG. Further research need to monitoring the quality of sediment.